Optimalisasi kesiapan guru Sekolah Dasar mengadapi Kurikulum Merdeka di SDN Sukaperna I Kecamatan Talaga Majalengka - Febby Fajar Nugraha; Gilang Kripsiyadi Praramdana; Pajar Anugrah Prasetio (IKIP SILIWANGI, 2023)
The rapid development of technology and the high needs of society demand a better curriculum reorientation. The independent curriculum is the answer to human needs in the world of education. The implementation of the independent curriculum in early 2022 has a positive impact on the development of the world of education because it answers the community's need for high-quality education. However, in its implementation, the independent curriculum needs acceleration in its implementation, currently, only the driving school facilitators are the spearhead of the independent curriculum socialization activities. With this, the school still feels confused about implementing the independent curriculum. The purpose of this activity program is to provide training and mentoring for teachers who are required to implement an independent curriculum in order to improve the quality of education in elementary schools. The method used in this Community Service is through a workshop, lecture, question and answer approach, and mentoring in implementing the independent curriculum, with the mentoring process expected to provide opportunities for teachers according to the training theme. This community service activity can provide direct benefits to partners in improving understanding and skills related to independent curriculum implementation activities, indicators of the success of community service activities are marked by the enthusiasm of the teachers in participating in training activities.